1)x^2+9x+8 (x+1)(x+8) (x+8)
==
3x^2+8x+5 3(x+1)(x+1 2/3) 3x+5
x^2+9x+8=0 3x^2+8x+5=0
D= 8^2-4*3*5=64-60=4
x1+x2=-9| -8(+)-))2
x1,2=
|-8;-1 6
x1x2=8 | x1=-1 ; x2=-1 2/3
2)
a)x(x+3)-4(x-5)=7(x+4)-8
x^2+3x-4x+20=7x+28-8
x^2-8x=0
x(x-8)=0
x=0 или х-8=0
х=8
б)2x^4-9x+4=0
D=(-9)^2-4*2*4=81-32=49
9(+(-))7
x1,2=
4
x1=4; x2=0.5
ответ:
разделим на 2 каждый член уравнения
\frac{\sqrt{3}}{2}sinx+\frac{1}{2}cos x =\frac{\sqrt{2}}{2}
2
3
sinx+
2
1
cosx=
2
2
\begin{lgathered}\frac{\sqrt{3}}{2}=cos{\frac{\pi}{6}}\\ \frac{1}{2}=sin{\frac{\pi}{6}}\\ sin(x+\frac{\pi}{6})=\frac{\sqrt{2}}{2}\\ x+\frac{\pi}{6} = \frac{\pi}{4}+2\pi n\\ x= -\frac{\pi}{6} + \frac{\pi}{4}+2\pi n\\ x = \frac{\pi}{12}+2\pi n\\ \\ x+\frac{\pi}{6} = \pi-\frac{\pi}{4}+2\pi n\\ x+\frac{\pi}{6} = \frac{3\pi}{4}+2\pi n\\ x=-\frac{\pi}{6} + \frac{3\pi}{4}+2\pi n\\ x = \frac{7\pi}{12}+2\pi {lgathered}
2
3
=cos
6
π
2
1
=sin
6
π
sin(x+
6
π
)=
2
2
x+
6
π
=
4
π
+2πn
x=−
6
π
+
4
π
+2πn
x=
12
π
+2πn
x+
6
π
=π−
4
π
+2πn
x+
6
π
=
4
3π
+2πn
x=−
6
π
+
4
3π
+2πn
x=
12
7π
+2πn
Объяснение:
х; у - цифры двухзначного числа
Система уравнений:
х+у=9
ху=18
х=9-у
(9-у)у=18
-у^2 +9у-18=0
у^2-9у+18=0
D=81-72=9
у1=(9-3)/2=7/2=3,5 - этот корень к условию задачи не подходит по смыслу;
у2=(9+3)/2=12/2=6
х=9-6=3
ответ: 36; 63.